Kelekatan Modal Sosial Pada Keluarga Santri Di Pulau Madura - Farahdilla Kutsiyah; Lukmanul Hakim; Ummu Kalsum (Institut Agama Islam Negeri Palopo, 2020)
AbstractA large capital owned by Pesantren (Islamic boarding schools) is the Ahlus sunnah waljamaah values which are juxtaposed with local wisdom. Madura Island is known as the island of a thousand Pesantren. Its existence affects the social structure and interaction of people on the island of Madura, where the resources embedded on them are called social capital. This study uses the librarian research and personal observation at several location points in Madura Island. The results showed that the attachment of Pesantren's social capital on santri families in Madura Island was the norm namely obedience to Kiai (religious leaders of Islamic boarding schools), barokah (divine blessing), high solidarity among fellow santri and simplicity. Networks such as recitation (koloman), alumnus ties, Istighozah (praying together for proposing forgiveness and hope), togetherness